2015
DOI: 10.3989/gya.1180142
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of oligoglycerol fatty acid esters preparation catalyzed by Lipozyme 435

Abstract: Oli goglycerol fatty acid esters (OGEs) are an important kind of polyglycerol fatty acid esters (PGEs) which have been widely used as emulsifiers in food, medicine and cosmetic industries. The aim of this study was to investigate the preparation of OGEs by the esterification of olig oglycerol with linoleic acid in a solvent-free system using Lipozyme 435 as the catalyst. The effects of substrate molar ratio, reaction time, reaction temperature, enzyme dosage, and water addition on the efficiency of esterificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…is result indicated that the enzymatic transesterification of decaglycerol and methyl laurate in this experiment has excellent monoester selectivity, consistent with our previous results about the lipase-catalytic production of glycerol monolaurate by transesterification of glycerol and methyl laurate [24]. However, the oligoglycerol fatty acid esters enzymatically prepared by the esterification of oligoglycerol (mainly composed of diglycerol, triglycerol, and tetraglycerol) and linoleic acid always give mixtures of monoesters, diesters, triesters, and tetraesters [12]. Figure 7 showed the surface tension (c) profiles of the aqueous solutions of decaglycerol laurates at 25°C.…”
Section: Esi-ms Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…is result indicated that the enzymatic transesterification of decaglycerol and methyl laurate in this experiment has excellent monoester selectivity, consistent with our previous results about the lipase-catalytic production of glycerol monolaurate by transesterification of glycerol and methyl laurate [24]. However, the oligoglycerol fatty acid esters enzymatically prepared by the esterification of oligoglycerol (mainly composed of diglycerol, triglycerol, and tetraglycerol) and linoleic acid always give mixtures of monoesters, diesters, triesters, and tetraesters [12]. Figure 7 showed the surface tension (c) profiles of the aqueous solutions of decaglycerol laurates at 25°C.…”
Section: Esi-ms Analysissupporting
confidence: 91%
“…e enzymatic esterification of polyglycerol and fatty acids to give PGFE has been carried out using lipase [10,11]. Using diglycerol and oleic acid as starting materials, acid conversion of about 90% and monoester selectivity of >94% have been achieved as the best results [12]. However, the PGFE preparations through the transesterification of polyglycerol and fatty acid esters were rarely reported in the literature [13].…”
Section: Introductionmentioning
confidence: 99%
“…The middle layer comprised the enzyme, which could be isolated by filtration and used repeatedly; the lower layer comprised the polyglycerol, which could be used as raw material. The upper layer comprised the mixture of synthesized polyglycerol fatty acid esters, which were determined according to the EE calculation as follows: where AV 0 is the acid value of rice-bran oil, C. camphora seed oil, or acetic acid, and AV is the acid value of the upper oil phase after the reaction. All determinations were carried out in duplicate and the average values were reported.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 In a previous study, Wan et al exploited oligoglycerol with linoleic acid in a solvent-free system using Lipozyme 435 as the catalyst to synthesis oligoglycerol fatty acid esters (OGEs). 12 Under the optimum conditions (reaction time of 4.52 h, reaction temperature of 90 °C, and enzyme dosage of 2 wt %), the experimental efficiency of esterification (EE) reached 95.82 ± 0.22%. However, there are few reports on how the chain lengths of fatty acids affect the hydrophilic−lipophilic balance (HLB), thereby affecting the emulsifying properties of the PGFEs.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation